Modulation of Seismic Attenuation at Parkfield, Before and After the 2004 M6 Earthquake. Issue 6 (26th June 2019) - Malagnini, L.; Dreger, D.S.; Bürgmann, R.; Munafò, I.; Sebastiani, G.
Abstract: The crack density within a fault's damage zone is thought to vary as seismic rupture is approached, as well as in the postseismic period. Moreover, external stress loads, seasonal or tidal, may also change the crack density in rocks, and all such processes can leave detectable signatures on seismic attenuation. Here we show that attenuation time histories from the San Andreas Fault at Parkfield are affected by seasonal loading cycles, as well as by 1.5–3‐year periodic variations of creep rates, consistent with Turner et al. (2015, https://doi.org/10.1002/2015JB011998 ), who documented a broad spectral peak, between 1.5 and 4 years, of the spectra calculated over the activity of repeating earthquakes, and over InSAR time series. After the Parkfield main shock, we see a clear modulation between seismic attenuation correlated to tidal forces. Opposite attenuation trends are seen on the two sides of the fault up to the M 6.5 2003 San Simeon earthquake, when attenuation changed discontinuously, in the same directions of the relative trends. Attenuation increased steadily of over one year on the SW side of the San Andreas Fault, until the San Simeon earthquake, whereas it decreased steadily on the NE side of the San Andreas Fault, roughly for the six months prior to the event. Random fluctuations are observed up to the 2004 M 6 Parkfield main shock, when rebounds in opposite directions are observed, in which attenuation decreased on the SW side, and increased on the NE side. Key Points: Seismic attenuation fluctuates with periods related to solid tides and seasonal loading, indicating strong sensitivity to stress changes Attenuation on the opposite sides of the San Andreas Fault shows mirror‐like anomalies before and after the 2004 Parkfield main shock Earthquake‐induced damage increases the sensitivity of seismic attenuation to periodic stress fluctuations